3D-printed strontium-doped BG-CaSiO3-HA composite scaffolds promote critical bone defect repair by improving mechanical strength and increasing osteogenic activity. Issue 12 (15th June 2023) - Dai, Kun; Yang, Zhen; Ding, Lin; Yang, Zhengyu; Hang, Fei; Cao, Xiaodong; Chen, Dafu; Zhao, Fujian; Chen, Xiaofeng
Abstract: The release of silicon and calcium elements contained in silicon-based materials promotes the formation of bone. For bioactive glass prepared by the sol-gel method, water-soluble binders are usually added when preparing 3D printed scaffolds. However, the obtained scaffolds are prone to collapse when exposed to water and have low strength. At the same time, the binder needs to be removed for clinical applications, so the 3D printed scaffolds need to be sintered. Under high temperature, bioactive glass scaffolds will be transformed into composite scaffolds composed of bioglass, CaSiO3 and hydroxyapatite, while different sintering temperatures will form different crystal types of CaSiO3 . In this study, SrBG-βCS-HA and BG-βCS-HA were obtained at a heating rate of 5 °C/min to 1100 °C and at the same rate to room temperature. SrBG-αCS-HA and BG-αCS-HA were obtained at a heating rate of 2 °C/min to 1200 °C and at the same rate to room temperature. In vitro and in vivo experiments verified that the presence of strontium in the obtained scaffolds after sintering further enhanced the osteogenic properties of the scaffolds. SrBG-αCaSiO3 -HA and SrBG-βCaSiO3 -HA were found to have relatively better osteogenic properties. The results show that SrBG-CaSiO3 -HA 3D printing scaffolds have excellent clinical application potential.